2012
DOI: 10.1021/ic3024056
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Pentanuclear Mesocate versus Octanuclear Helicate: Size Effect of the [MII33-O/X)]n+ Triangle Core

Abstract: The first cluster mesocate (H(3)O)[{Fe(2)(μ-L)(3)}{Fe(3)(μ(3)-O)(μ-Cl)(3)}]·3EtOH (1) and a new series of cluster helicates, [{Mn(μ-L)(3)}(2){Mn(3)(μ(3)-Cl)}(2)](ClO(4))(2)·2MeOH·6H(2)O (2), [{Cd(μ-L)(3)}(2){Cd(3)(μ(3)-Br)}(2)]Br(2)·2DMF·14H(2)O (3), and [{Cd(μ-L)(3)}(2){Cd(3)(μ(3)-I)}(2)](CdI(4))·3H(2)O (4), have been synthesized by the self-assembly of a C(2)-symmetric tritopic ligand, 2,6-bis[5-(2-pyridinyl)-1H-triazol-3-yl]pyridine (H(2)L) with different metal halogen salts. Single-crystal X-ray diffractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In this work, we synthesize two grid-type architectures supported by a polynitrogen heterocyclic ligand 2,6-bis[5-(2pyridinyl)-1H-triazol-3-yl]pyridine (H 2 L; Fig. 1), 15,18 which consists of three pyridyl rings linked by two triazolyl groups. The hydrothermal reaction of CuI with H 2 L and NH 3 $H 2 O in methanol yielded an 11-membered mixed-valence copper cluster (complex 1).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we synthesize two grid-type architectures supported by a polynitrogen heterocyclic ligand 2,6-bis[5-(2pyridinyl)-1H-triazol-3-yl]pyridine (H 2 L; Fig. 1), 15,18 which consists of three pyridyl rings linked by two triazolyl groups. The hydrothermal reaction of CuI with H 2 L and NH 3 $H 2 O in methanol yielded an 11-membered mixed-valence copper cluster (complex 1).…”
Section: Introductionmentioning
confidence: 99%
“…The coordination sphere of Mn II can be viewed as a slightly distorted octahedron. The Mn1Cl1 axial bond lengths (2.522(3) Å) fall in the normal range; however, these bond lengths are longer than the previously reported MnCl bond lengths (an average MnCl bond length of 2.41 Å) in the triazole–Mn II coordination polymer of [{Mn(μ‐L) 3 } 2 {Mn 3 (μ 3 ‐Cl)} 2 ](ClO 4 ) 2 ⋅ 2 MeOH ⋅ 6 H 2 O (L=2,6‐bis[5‐(2‐pyridinyl)‐1 H ‐ triazol‐3‐yl]pyridine) 15…”
Section: Resultsmentioning
confidence: 67%
“…Discrete and polymeric oxide-centered triangular [M 3 O(O 2 CR) 6 L 3 ] n+ complexes and/or aggregated triangular {Mn 3 O} units as well as heterometallic {Mn 2 MO} or {Fe 2 MO} (M = transition metal) have been reported for other transition metals [36][37][38][39][40]. A Mn 8 helicate complex featuring two μ 3 -Cl bridged Mn II 3 scalene triangles in which the Cl atom deviates slightly from the Mn 3 plane has been reported [41]. Moreover, Christou et al have reported a near-equilateral Mn III 3 triangle capped by μ 3 -O 2ion derived from the H 3 L Me proligand [40].…”
Section: Structural Description Of Coordination Clusters (2) and (3)mentioning
confidence: 96%